The Effect of Tax Planning, Intellectual Capital, Financial Performance, and Good Corporate Governance (GCG) on Earnings Management. - Rivaldo Martua; Rifkiansyah al Hafiz (Journal of Accounting and Auditing, 2026)
Purpose – This research aims to analyze the influence of tax planning, intellectual capital, financial performance and Good Corporate Governance (GCG)  on profit management, in basic materials, consumer non-cyclicals, and infrastructures sector companies listed on the Indonesia Stock Exchange (BEI) for the period 2022-2024. Design/methodology/approach – This research uses a quantitative approach with the panel data regression method. The research sample consists of 44 property and real estate companies that meet the purposive sampling criteria, resulting in 132 observations during the period 2022-2024. Data analysis using Eviews 9 software Findings – The results of the study are expected to show that tax planning, intellectual capital, financial performance and Good Corporate Governance have an influence on earnings management practices. Research limitations/implications – This research has limitations in the relatively short observation period, namely 2022-2024, and is limited to certain industrial sectors. In addition, the research only used quantitative data and did not consider non-financial factors. The implications of this research are expected to be an input for company management in improving the quality of governance as well as for regulators in strengthening supervision of financial reporting practices.